Be the serpent ebook - McGuire, Seanan (October Daye, 2022)
Now in hardcover, the sixteenth novel of the Hugo-nominated, New York Times -bestselling October Daye urban fantasy series. October Daye is finally something she never expected to be: married. All the trials and turmoils and terrors of a hero’s life have done very little to prepare her for the expectation that she will actually share her life with someone else, the good parts and the bad ones alike, not just allow them to dabble around the edges in the things she wants to share. But with an official break from hero duties from the Queen in the Mists, and her family wholly on board with this new version of “normal,” she’s doing her best to adjust.   It isn’t always easy, but she’s a hero, right? She’s done harder.   Until an old friend and ally turns out to have been an enemy in disguise for this entire time, and October’s brief respite turns into a battle for her life, her community, and everything she has ever believed to be true.    The debts of the Broken Ride are coming due, and whether she incurred them or not, she’s going to be the one who has to pay.